Review of the fish-parasitic genus Cymothoa Fabricius, 1793 (Crustacea: Isopoda: Cymothoidae) from Australia - Martin, Melissa B.; Bruce, Niel L.; Nowak, Barbara F. (Zootaxa, 2016)
The genus Cymothoa Fabricius, 1793 is revised for Australian waters. Cymothoa hermani Hadfield, Bruce & Smit, 2011, previously known from Tanzania on the host Selar crumenophthalmus (Bloch, 1793) is new to Australian waters. Cymothoa carangi Avdeev, 1979; Cymothoa epimerica Avdeev, 1979; Cymothoa parupenei Avdeev, 1979; Cymothoa propria Avdeev, 1979; Cymothoa rotunda Avdeev, 1979 and Cymothoa pulchrum Lanchester, 1902 are redescribed. Cymothoa curta Schioedte & Meinert, 1884, first described from the host Anableps anableps (Linnaeus, 1758); and Cymothoa plebeia Schioedte & Meinert, 1884, first described from Cape Verde; are redescribed and excluded from the Australian fauna. Cymothoa limbata Schioedte & Meinert, 1884 is placed into junior synonymy with Cymothoa eremita (Brünnich, 1783). A key to the Australian species of Cymothoa is presented.